Carbon neutrality in the residential sector: a general toolbox and the case of Germany - Anna Hornykewycz; Jakob Kapeller; Jan David Weber; Bernhard Schütz; Lukas Cserjan (npj Climate Action)
Abstract This paper presents a general framework for estimating the renovation and investment requirements associated with a socio-ecological transformation of the residential sector that effectively reduces the net emissions of the residential sector (close) to zero. The framework takes ecological and distributional considerations into account and aims to provide concrete outcomes suitable to inform policy-making, while being as parsimonious as possible on the side of data requirements. All key steps associated with this framework are compiled in an openly accessible toolbox that can be adapted to different country-specific contexts. This paper takes the German case as an example to illustrate the main assumptions, data requirements, and outcomes that can be derived from this toolbox.